Cardiac Rehabilitation Increases SIRT1 Activity and β-Hydroxybutyrate Levels and Decreases Oxidative Stress in Patients with HF with Preserved Ejection Fraction. (27th November 2019) - Corbi, Graziamaria; Conti, Valeria; Troisi, Jacopo; Colucci, Angelo; Manzo, Valentina; Di Pietro, Paola; Calabrese, Maria Consiglia; Carrizzo, Albino; Vecchione, Carmine; Ferrara, Nicola; Filippelli, Amelia
Abstract : Purpose . Exercise training induces beneficial effects also by increasing levels of Sirtuin 1 (Sirt1) and β -hydroxybutyrate ( β OHB). Up to date, no studies investigated the role of exercise training-based cardiac rehabilitation (ET-CR) programs on β OHB levels. Therefore, the present study is aimed at investigating whether a supervised 4-week ET-CR program was able to induce changes in Sirt1 activity and β OHB levels and to evaluate the possible relationship between such parameters, in Heart Failure with preserved Ejection Fraction (HFpEF) patients. Methods . A prospective longitudinal observational study was conducted on patients consecutively admitted to the Cardiology and Cardiac Rehabilitation Units of "San Gennaro dei Poveri" Hospital in Naples, Italy. In fifty elderly patients affected by HFpEF, in NYHA II and III class, Sirt1 activity, Trolox Equivalent Antioxidant Capacity (TEAC), β OHB, and Oxidized Low-Density Lipoprotein (Ox-LDL) levels were measured before and at the end of the ET-CR program. A control group of 20 HFpEF patients was also recruited, and the same parameters were evaluated 4 weeks after the beginning of the study. Results . ET-CR induced an increase of Sirt1 activity, β OHB levels, and antioxidant capacity. Moreover, it was associated with a rise in NAD + and NAD + /NADH ratio levels and a reduction in Ox-LDL. No changes affected the controls. Conclusion . The characterization of the ET-CR effects from a metabolic viewpoint might represent an important step to improve the HFpEF management.